Little Leaf Notcher (suggested common name) Artipus floridanus Horn (Insecta: Coleoptera: Curculionidae) - Angela Gabrielle LaTora; Adam Dale (EDIS)
Artipus floridanus Horn, also known as the little leaf notcher, is a secondary pest of citrus and several ornamental plants in Florida and the Caribbean. This species is in the order Coleoptera, the beetles, and the family Curculionidae, the weevils and snout beetles. It was first described by Horn in 1876 (Poole 1996). https://edis.ifas.ufl.edu/in1264